Leituras de si: saberes docentes e história de vida de formadores de professores - REIS JÚNIOR, Leandro Passarinho (Universidade Federal do Paraná, 2023)
This essay deals with the nature of the teaching knowledge of teacher trainers of the University Campus of Castanhal/UFPA through life histories. The objective was to analyze how the teacher educators are constituted and how they generate and perceive the nature and mobilization of their teacher knowledge in the training practice. Three life histories were used to unveil the lived, constructed, shared and reflected knowledge in teaching. The treatment of the narrative episodes occurred in the light of the biographical methodology, using the thematic life history of spaces and formative times, in an interpretative analysis. The results showed that teacher knowledge fecundates and develops in the formative trajectory of the teacher, covering the personal and professional dimension of his life, thus composing his history in a critical reading of himself.